Endoplasmic Reticulum Stress Contributes to Ventilator-Induced Diaphragm Atrophy and Weakness in Rats - Li, Shaoping; Luo, Guanguan; Zeng, Rong; Lin, Lian; Zou, Xingnan; Yan, Yu; Ma, Haoli; Xia, Jian; Zhao, Yan; Zhou, Xianlong (Frontiers in Physiology, 2022)
Background: Accumulating evidence indicates that endoplasmic reticulum (ER) stress plays a critical role in the regulation of skeletal muscle mass. In recent years, much attention has been given to ventilator-induced diaphragm dysfunction (VIDD) because it strongly impacts the outcomes of critically ill patients. Current evidence suggests that the enhancement of oxidative stress is essential for the development of VIDD, but there are no data on the effects of ER stress on this pathological process. Methods: VIDD was induced by volume-controlled mechanical ventilation (MV) for 12 hours; Spontaneous breathing (SB, for 12 h) rats were used as controls. The ER stress inhibitor 4-phenylbutyrate (4-PBA), the antioxidant N-acetylcysteine (NAC), and the ER stress inducer tunicamycin (TUN) were given before the onset of MV or SB. Diaphragm function, oxidative stress, and ER stress in the diaphragms were measured at the end of the experiments. Results: ER stress was markedly increased in diaphragms relative to that in SB after 12 hours of MV (all P < 0.001). Inhibition of ER stress by 4-PBA downregulated the expression levels of proteolysis-related genes in skeletal muscle, including Atrogin-1 and MuRF-1, reduced myofiber atrophy, and improved diaphragm force-generating capacity in rats subjected to MV (all P < 0.01). In addition, mitochondrial reactive oxygen species (ROS) production and protein level of 4-HNE (4-hydroxynonenal) were decreased upon 4-PBA treatment in rats during MV (all P < 0.01). Interestingly, the 4-PBA treatment also markedly increased the expression of peroxisome proliferator-activated receptor-gamma co-activator-1alpha (PGC-1α) (P < 0.01), a master regulator for mitochondrial function and a strong antioxidant. However, the antioxidant NAC failed to reduce ER stress in the diaphragm during MV (P > 0.05). Finally, ER stress inducer TUN largely compromised diaphragm dysfunction in the absence of oxidative stress (all P < 0.01). Conclusion: ER stress is induced by MV and the inhibition of ER stress alleviates oxidative stress in the diaphragm during MV. In addition, ER stress is responsible for diaphragm dysfunction in the absence of oxidative stress. Therefore, the inhibition of ER stress may be another promising therapeutic approach for the treatment of VIDD.